The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajpcell.00129.2015
|View full text |Cite
|
Sign up to set email alerts
|

miR-148a-3p overexpression contributes to glomerular cell proliferation by targeting PTEN in lupus nephritis

Abstract: The objective of this study was to investigate the role of miR-148a-3p in lupus nephritis (LN) based on data from previous studies and a microRNA assay. We evaluated the miR-148a-3p expression level in LN renal tissues and blood serum to determine its clinicopathological significance and effect on glomerular cell proliferation. Then, we collected renal glomeruli from LN mice and determined the miR-148a-3p, proliferating cell nuclear antigen (PCNA), and PCNA/Thy1 expression. We performed functional analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 34 publications
(40 reference statements)
3
41
0
2
Order By: Relevance
“…miR‐151‐3p functions as a key regulator in epithelial‐to‐mesenchymal transition (EMT), innate immunity, and inflammation, which is concordant with the fact that H pylori infection unavoidably triggers immune response and inflammation. In addition, miR‐148a‐3p played important roles in restraining cell proliferation and EMT . Taken together, these facts indicate that H pylori infection involves in multiple biological processes that are collectively mediated by these miRNAs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…miR‐151‐3p functions as a key regulator in epithelial‐to‐mesenchymal transition (EMT), innate immunity, and inflammation, which is concordant with the fact that H pylori infection unavoidably triggers immune response and inflammation. In addition, miR‐148a‐3p played important roles in restraining cell proliferation and EMT . Taken together, these facts indicate that H pylori infection involves in multiple biological processes that are collectively mediated by these miRNAs.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, miR-148a-3p played important roles in restraining cell proliferation and EMT. [31][32][33] Taken together, these facts indicate that H pylori infection involves in multiple biological processes that are collectively mediated by these miRNAs.…”
Section: Discussionmentioning
confidence: 87%
“…26 In this regard, Qingjuan et al recently reported that miR-148a could directly bind to the 3 0 -UTR of PTEN and reduce the expression of PTEN in lupus nephritis, resulting in accelerated glomerular cell proliferation and tumor progression. 27 However, to introduce miRNAs into the clinical practice, more research is needed to identify their target mRNAs and understand their functions, as they harbor both oncogenic and tumor suppressive characteristics. The different features of miRNAs suggest that they act on multiple targets in different cellular processes that contribute to PCa development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to explore whether miR-148a could, by modulating (P)RR-mediated functions, such as regulating lipid metabolism, maintaining V-ATPase integrity, and activating tissue RAS, contribute to the onset and progression of such diseases. Among these diseases, it is interesting to notice that plasma miR-148a levels were elevated in LN patients and mice [37]. LN patients have higher risks for ischemic heart diseases [38,39], which is likely caused by abnormalities in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%